Flypaper Effect Pada Dana Alokasi Umum Dan Dana Alokasi Khusus Terhadap Belanja Daerah Dengan Pendapatan Asli Daerah Sebagai Variabel Moderasi (Studi Pada Pemerintah Kabupaten Aceh Tamiang) - Nur Ainun; Afrah Junita; Muhammad Salman (Ekonomi Bisnis Manajemen dan Akuntansi (EBMA), 2023)
This study aims to determine the effect of the Flypaper Effect on General Allocation Funds and Special Allocation Funds on Regional Expenditures with Regional Original Income as a Moderating Variable (Case Study in the Government of Aceh Tamiang District). The population of this study is in the form of Regional Expenditures, General Allocation Funds (DAU), Special Allocation Funds (DAK) and Regional Original Income (PAD) in 2014-2021 in Aceh Tamiang District. The sampling technique uses the Saturated Sample method where all members of the population are used as samples. The sample in this study is in the form of realization reports regarding Regional Expenditures, General Allocation Funds (DAU), Special Allocation Funds (DAK) and Regional Original Income (PAD) in 2014-2021 in Aceh Tamiang District, so the number of observations is 8 years. The data analyzed in this study is the documented realization of the Regional Expenditure Budget (APBD) from the Aceh Tamiang Regional Financial Management Agency (BPKD) and the Directorate General of Fiscal Balance (DJPK) website. The results showed that partially the Allocation Fund variable had a positive and significant effect on regional spending in Aceh Tamiang District. Meanwhile, the special allocation fund variable is not significant for regional spending in Aceh Tamiang District. Regional original income has no significant effect on regional spending. Partially local revenue cannot moderate the relationship of general allocation funds to regional spending in Aceh Tamiang district. Partially local revenue cannot moderate the relationship of special allocation funds to regional spending in Aceh Tamiang district. Finally, general allocation funds, special allocation funds, and local revenues together have a positive and significant effect on regional spending in Aceh Tamiang District.